Hemocompatibility of titania nanotube arrays under static and dynamic conditions - Ghosh, Sayudh, author; Popat, Ketul C., advisor; Wang, Zhijie, committee member; Li, Yan, committee member (Colorado State University. Libraries, 2020)
Titanium and titanium alloys have been extensively used to make blood contacting medical devices such as vascular stents, mechanical heart valves, etc. However, the material is not always hemocompatible, often resulting in thrombosis and eventual rejection of the medical device. To overcome this, medical practitioners have used anti coagulating methods which have had other detrimental effects on patients. Researchers have tried to overcome this problem by developing different surfaces for materials and evaluating hemocompatibility in static conditions, however it is important to evaluate hemocompatibility under dynamic conditions to get a realistic biological response. Recent studies have shown that nanotextured surfaces show better hemocompatibility than non-nanotextured surfaces. In this study, we have developed a dynamic chamber to evaluate hemocompatibility of titania nanotube arrays. The nanotube arrays were fabricated using anodization technique and modified to make the surface either supherhydrophobic or superhydrophillic. The stability of these surfaces and their interaction with blood and its components (protein adsorption, cell adhesion, platelet adhesion and activation) was investigated under dynamic flow conditions and compared to that from static conditions. The results indicate that the Titania nanotube arrays that were superhydrophobic show significantly enhanced hemocompatibility than other surfaces.
Keywords: dynamic blood flow; protein adsorption; titania nanotubes; hemocompatibility; cell adhesion; superhemophobic